A DLTS study of a ZnO microwire, a thin film and bulk material. Issue 1633 (2014) - Schmidt, Florian; Schlupp, Peter; Müller, Stefan; Dietrich, Christof Peter; von Wenckstern, Holger; Grundmann, Marius; Heinhold, Robert; Kim, Hyung-Suk; Allen, Martin Ward
ABSTRACT: We have investigated the electrical properties of a ZnO microwire grown by carbo-thermal evaporation, a ZnO thin film grown by pulsed-laser deposition on an a -plane sapphire, and a hydrothermally grown Zn-face ZnO single crystal (Tokyo Denpa Co. Ltd.). The samples were investigated by means of current-voltage measurements, capacitance-voltage measurements, and deep-level transient spectroscopy. The defects T2 [1, 2] and E3 [1, 3, 4] were identified in all three sample types. Additionally, in the single crystal and thin film samples E64 [5] and E4 [1] were detected. These findings support the common opinion that T2 is an intrinsic defect since it is found in all the samples investigated and thus its occurrence is not related to any growth technique.